Complex, Contrastive Multi-Paradigmal Studies for Studying Expressive Means in the Translation of Journalistic Texts from English to Ukrainian - Melnychuk, Roksolana; Terekhova, Svitlana; Zinchenko, Hanna; Kuzmenko, Natalia; Valuieva, Nataliia (Bilingual Publishing Group, 2024)
The aim of the research is to determine the effectiveness of polyparadigm analysis for studying the transfer of expressive means in the translation of journalistic texts from English to Ukrainian. The research employed content analysis, the method of analysis of linguistic action, translation evaluation by experts. The frequency of use of expressive means, the comparison of the length of sentences, the comparison of the lexical diversity of the original English text and its Ukrainian translation were used for statistical data processing. The t-test, chi-square, congruence index were also used. Publicists use a wide range of expressive vocabulary to make their articles more interesting, emotional, and persuasive. Expressive vocabulary emphasizes the weight and significance of facts, creates an emotional effect, emphasizes the novelty or revolutionary nature, and also warns about the potential danger or tragedy of the situation. The translation of expressive vocabulary from English to Ukrainian is difficult, as it is important to convey not only the exact meaning of the word, but also its emotional colour. The results obtained in this way show the high efficiency of polyparadigm analysis for the study of expressive means. Prospects for further research include the development of new technologies for automatic translation that take into account the expressive means of language. This can help to ensure a more accurate and emotionally rich translation of journalistic texts.
Keywords: polyparadigm analysis; Journalistic Discourse; International Press; Content Analysis; Accurate Translation